Penerapan Strategi Pembelajaran Bermain Peran dalam Meningkatkan Motivasi dan Prestasi Belajar Siswa Bidang Studi Biologi Kelas XI IPA 1 MAN 1 Serang - Mulyani, Refliyanti; Nihan, Aditya Rahman Kintu (JUPE : Jurnal Pendidikan Mandala, 2023)
This classroom action research aimed to determine whether the implementation of role-playing learning in class XI IPA 1 MAN 1 Serang increased student motivation and achievement in biology learning. In the 2019-2020 academic year, it is anticipated that this study's results will provide knowledge closely related to role-playing learning strategies that can increase motivation and achievement in studying biology in class XI IPA 1 MAN 1 Serang. Based on the results of the data analysis, it can be concluded that the application of role-playing learning strategies in biology subjects about the circulatory system in humans can increase motivation and achievement in class XI IPA 1 MAN 1 Serang during the 2019-2020 academic year. Averaging 67.30 cycles I and 70.64 cycles II, whereas the classical completeness is 71.79 cycles I and 87.17 cycles II.